GEOCHRONOLOGY OF ZIRCON MEGACRYSTS FROM NEPHELINE-BEARING GNEISSES AS CONSTRAINTS ON TECTONIC SETTING: IMPLICATIONS FOR RESETTING OF THE U-PB AND LU-HF ISOTOPIC SYSTEMS - Ashwal L.D.; Armstrong R.A.; Roberts R.J.; Schmitz M.D.; Corfu F.; Hetherington C.J.; Burke K.; Gerber M. (My University, 2007)
Nepheline-bearing gneisses from the 75 km2 Tambani body in the Mozambique Belt of southern Malawi, are miaskitic biotite-nepheline monzodiorites, reflecting an absence of K-feldspar, alkali amphiboles or pyroxenes, and contain euhedral zircon megacrysts up to 5 cm across. The zircons contain U = 1–1,860 ppm, Th = 0–2,170 ppm and Y = 400–1,100 ppm, and very low concentrations of all other measured trace elements except Hf (HfO2 =  0.53–0.92 wt. %). Cathodoluminescence images reveal oscillatory sector growth zoning and no evidence for xenocrystic cores, indicating that the zircons represent primary magmatic crystallization products that have survived amphibolite grade metamorphism. U-Pb isotopic analyses (by TIMS) yield an upper intercept age of 730 ± 4 Ma (MSWD = 1.7), which we interpret as the time of magmatic crystallization of the zircons. This is coincident with 11 SHRIMP spot analyses, which yield a mean age of 729 ± 7 Ma (MSWD = 0.37). Metamorphism, at 522 ± 17 Ma as suggested by monazite, caused partial Pb-loss during local recrystallization of zircon. Lu-Hf isotopic data for three whole-rock samples of nepheline-bearing gneiss are collinear with those for zircon megacrysts, and correspond to an age of 584 ± 17 Ma (MSWD = 0.37. We interpret the Lu-Hf array to represent a mixing line defined by the Hf isotopic signature of primary zircon and that of the rock-forming minerals reset during metamorphic (re-)crystallization; hence the 584 Ma age is likely geologically meaningless. Given the well-defined association of nepheline syenites (and phonolitic volcanic equivalents) with continental rifting, we suggest that the Tambani body represents a magmatic product formed at 730 Ma during the break-up of the Rodinia supercontinent. The 522 Ma age is akin to other Pan-African metamorphic ages that record collisional suturing events during the final assembly of Gondwana. Zircon-bearing nepheline gneisses thus preserve a record of intra-continental rifting and of continental collision in southern Malawi.
Keywords: ZIRCON; HFO2; NEPHELINE; NEPHELINE SYENITE; ISOCHRON